Analisis Teknik Penerjemahan Tindak Tutur Komisif Dalam Novel Central Park Karya Guillaume Musso - Egidhia Dwi Tiara Khusnanda; Iim Siti Karimah; Ariessa Racmadhany (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
Studies on commissive speech acts in modern French literary texts are still very limited, especially in the context of their translation into Indonesian. However, commissive speech acts such as promises, offers, oaths, and threats play an important role in building the dynamics of relationships between characters in a narrative. Therefore, this research is important to fill the gap in studies and enrich translation studies within the context of pragmatic linguistics. This research employs a qualitative descriptive method with a document analysis approach on Guillaume Musso's novel Central Park and its Indonesian translation. This study refers to Austin's (1962) and Searle's (1969) speech act theory to identify forms of commissive speech acts, as well as Vinay and Darbelnet's (1995) translation technique theory to analyze the translation strategies used. The research questions are answered through the identification of the types of commissive speech acts that appear in the translated text and the translation techniques used to convey the meaning of the utterances into the target language. The results of the study show that out of 51 data analyzed, four types of commissive speech acts were found, namely promises (49%), offers (31.3%), oaths (11.8%), and threats (7.9%). Meanwhile, in terms of translation techniques, six out of seven techniques proposed by Vinay and Darbelnet were identified, with modulation being the most dominant technique (35.3%). These results indicate that translators actively adapt the meaning and function of utterances to align with the cultural and linguistic context of the target language.